Development of peer teaching based on differentiation using QR code in Islamic education at SMP IT Al-Ulum Medan - Siregar, Tasya Amelia Putri; Salminawati, Salminawati; Dahlan, Zaini (Jurnal Penelitian Pendidikan, 2024)
This study aims to analyze the development stage, validity, and effectiveness of differentiation-based peer teaching strategies through QR Code learning media in Islamic Religious Education (PAI) subjects at Al Ulum Terpadu Medan Islamic Middle School. The research method used in this study is the Borg and Gall Research and Development Method which aims to understand the urgent needs to be met by a community group, then studied in depth regarding the causes and theories that support solving the problem and then used as a basis for product development, validation, and effectiveness testing. Product development in this study was carried out directly in the classroom through the process before, during, and after the research involving Islamic religious group teachers and students. Peer tutoring approach has been done to develop students’ collaboration ability in differentiated learning for Abbasiyah Dynasty learning achievement in class VIII of SMP Islam Al Ulum Terpadu Medan, there was a significant increase from cycle I and cycle II. This is indicated by an increase in the percentage of learning implementation achievement of 12.50%, collaboration ability of 37.50% and student learning outcomes at the cognitive level of 39.50%. The assessment results from the validator stated that the development of technology-based differentiated learning media for class VII procedural text material was declared valid with an average percentage of 88.43%. Peer tutors can be an alternative solution to problems in differentiated learning because they can help teachers in assisting the process of developing unique and diverse student potentials. Teachers often find it difficult to convey activity steps so they need to empower tutors as message deliverers, help provide repeated explanations, patiently direct friends, and guide friends in learning activities to achieve learning goals.
Keywords: differentiation; islamic religious education; peer teaching; qr code